NatB-Mediated N-Terminal Acetylation Affects Growth and Biotic Stress Responses. Issue 2 (19th November 2019) - Huber, Monika; Bienvenut, Willy V.; Linster, Eric; Stephan, Iwona; Armbruster, Laura; Sticht, Carsten; Layer, Dominik; Lapouge, Karine; Meinnel, Thierry; Sinning, Irmgard; Giglione, Carmela; Hell, Ruediger; et al.
Abstract : Initiator methionine acetylation by NatB is evolutionary conserved and critical for abiotic stress responses in Arabidopsis thaliana. Abstract: N ∝ -terminal acetylation (NTA) is one of the most abundant protein modifications in eukaryotes. In humans, NTA is catalyzed by seven N α -acetyltransferases (NatA–F and NatH). Remarkably, the plant Nat machinery and its biological relevance remain poorly understood, although NTA has gained recognition as a key regulator of crucial processes such as protein turnover, protein-protein interaction, and protein targeting. In this study, we combined in vitro assays, reverse genetics, quantitative N -terminomics, transcriptomics, and physiological assays to characterize the Arabidopsis ( Arabidopsis thaliana ) NatB complex. We show that the plant NatB catalytic (NAA20) and auxiliary subunit (NAA25) form a stable heterodimeric complex that accepts canonical NatB-type substrates in vitro. In planta, NatB complex formation was essential for enzymatic activity. Depletion of NatB subunits to 30% of the wild-type level in three Arabidopsis T-DNA insertion mutants ( naa20-1, naa20-2, and naa25-1 ) caused a 50% decrease in plant growth. A complementation approach revealed functional conservation between plant and human catalytic NatB subunits, whereas yeast NAA20 failed to complement naa20-1 . Quantitative N-terminomics of approximately 1000 peptides identified 32 bona fide substrates of the plant NatB complex. In vivo, NatB was seen to preferentially acetylate N termini starting with the initiator Met followed by acidic amino acids and contributed 20% of the acetylation marks in the detected plant proteome. Global transcriptome and proteome analyses of NatB-depleted mutants suggested a function of NatB in multiple stress responses. Indeed, loss of NatB function, but not NatA, increased plant sensitivity toward osmotic and high-salt stress, indicating that NatB is required for tolerance of these abiotic stressors.